Measurement of Thermal Neutron Capture Cross Section and Resonance Integral for the \(^45\)Sc\((n,γ)^46\)Sc Reaction with Pulsed Neutrons - Do, Nguyen Van; Khue, Pham Duc; Thanh, Kim Tien; Hien, Nguyen Thi; Guinyun, Kim (Communications in Physics, 2014)
Thermal neutron capture cross section and resonance integral for the ^45Sc(n,γ )^46Sc reaction were measured by the activation method using the ^197Au(n,γ )^198Au reaction as a single comparator. The high-purity scandium and gold samples with and without Cd cover with the thickness of 0.5 mm were irradiated in a pulsed neutron field of the 100 MeV electron linac of the Pohang Accelerator Laboratory (PAL). The induced activities in the activated foils were measured with a well calibrated HPGe detector. In order to improve the accuracy of the experimental results the effect of the non-ideal epithermal spectrum was taken in to account by determining the neutron spectrum shape factor (α ), and the corrections for the thermal (G_th) and the resonance (G_epi) neutron self-shielding effects, the γ -ray attenuation (F_g) and the γ -ray coincidence summing effect were made. The thermal neutron cross-section for the ^45Sc(n,γ )^46Sc reaction has been determined to be σ _o = 27.6 ± 0.8 barn. By assuming the cadmium cut-off energy of 0.55 eV, the resonance integral for the ^45Sc(n,γ )^46Sc reaction has been determined to be I_o = 12.7 ± 0.7 bar. The present results are compared with the reference data and discussed.